Pertumbuhan dan produksi jagung manis (Zea mays saccharata) dengan pemupukan “Kotpi Plus” - Nyoman Adhitya Putra Dewangga; Dwi Retno Lukiwati; Budi Adi Kristanto (Journal of Agro Complex, 2018)
The research aimed to increase the quality of manure to “Kotpi Plus” and to study the effect on growth and yield of sweet corn. The research used monofactor randomized block design with six treatments and 5 replications. The treatments were T0. Control; T1. 100% “Kotpi Plus” + 0% Urea and TSP (UT); T2. 75% “Kotpi Plus” + 25% UT, T3. 50% “Kotpi Plus” + 50% UT; T4. 25% “Kotpi Plus” + 75% UT; and T5. 0% “Kotpi Plus” + 100% UT. Parameters measured were plant height, leaf number, cob length, cob weight with cornhusk, and sum of seed row in a cob. Data were subjected to analysis of variance and followed by DMRT at α = 5%. The result on plant height and leaf number showed that T4 167.7 cm was significantly higher compared to control and 8.21 leaves significantly higher compared to control and T1, respectively. “Kotpi Plus” combined with inorganic fertilizer produced cob length significantly higher compared to control. Cob weight with cornhusk on T4 was significantly higher compared to T0 and T1. The given of “Kotpi Plus” fertilizer was not affecting on sum of seed row in a cob. Keywords: Gliricidia sepium, growth, phosphate rock, sweet corn, yield.